Community College—A means to Meet the Needs of the Excluded in Higher Education - Gandhi, E. Arumuga (JOURNAL OF INDIAN EDUCATION, 2010)
At the end of the twentieth century a number of community colleges were established in Tamil Nadu to reduce the mismatch between education and employment. Roughly a decade has passed by since establishment of such colleges in Tamil Nadu and therefore, it is the right time to evaluate the functioning of such colleges in achieving the expected goal. The present paper is one such modest attempt made on community colleges to evaluate in terms of number of colleges started and their governance, their location, courses offered, students’ enrolment pattern in various courses and their pass-outs from 1998 – 2005. To facilitate the evaluation, an empirical study was conducted by making personal visits to some selected community colleges to understand the students’ perception towards such colleges and the findings are discussed in the paper.